2017
DOI: 10.3847/1538-4357/aa6a1e
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Mixing Length and Metallicity on the Giant Branch: Implications for Ages in the Gaia Era

Abstract: In the updated APOGEE-Kepler catalog, we have asteroseismic and spectroscopic data for over 3000 first ascent red giants. Given the size and accuracy of this sample, these data offer an unprecedented test of the accuracy of stellar models on the post-main-sequence. When we compare these data to theoretical predictions, we find a metallicity dependent temperature offset with a slope of around 100 K per dex in metallicity. We find that this effect is present in all model grids tested, and that theoretical uncert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
111
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 79 publications
(104 reference statements)
15
111
4
Order By: Relevance
“…In this work, six oscillating red giants in eclipsing binaries were used to calibrate these parameters for evolved stars. Our main conclusions from the results are summarised as follows: (i) The average mixing-length parameter of the six red giants is ∼ 1.14 ± 0.07 times the calibrated solar value, which is similar with the previous results based on the APOGEE sample (Tayar et al 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this work, six oscillating red giants in eclipsing binaries were used to calibrate these parameters for evolved stars. Our main conclusions from the results are summarised as follows: (i) The average mixing-length parameter of the six red giants is ∼ 1.14 ± 0.07 times the calibrated solar value, which is similar with the previous results based on the APOGEE sample (Tayar et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Their grid models for the red giants within the range of metallicity ([Fe/H]) from −0.5 to +0.4 required a ∼8% larger α than the Sun to fit the observations. Tayar et al (2017) also suggested a linear correlation between α and [Fe/H]. However, we did not obtain a clear dependence between the two parameters in our stars.…”
Section: The Mixing-length Parametercontrasting
confidence: 73%
“…These cases provide valuable opportunities to enhance our knowledge of stellar astrophysics by leveraging APOGEE-2 spectra together with complementary observations exploring other wavelength regimes and/or observational sampling. This is exemplified by recent results from the APOKASC (Tayar et al 2017) and CoRoGEE (Anders et al 2017) samples, and a plethora of additional opportunities lie with optical spectroscopic surveys such as GALAH (Martell et al 2017) and GES (Gilmore et al 2012). Targets selected to be in common with other data sets, spectroscopic and photometric, have the targeting bit APOGEE2_TARGET2=5 set, as well as bits for specific surveys ( Table 1).…”
Section: Cross-and Inter-survey Calibrationmentioning
confidence: 98%
“…In addition, 36 stars (12 in NGC 6791, 20 in NGC 6819, and 4 in NGC 6811) have new temperatures determined from spectroscopy with ASPCAP (APOGEE Stellar Parameters and Chemical Abundances Pipeline, Zasowski et al 2013;Nidever et al 2015;Holtzman et al 2015;García Pérez et al 2016;Majewski et al 2017), using the Data Release 13 (DR13, SDSS Collaboration 2016) of SDSS IV (Blanton et al 2017), which includes the post-release metallicity correction (see Holtzman et al, in prep.). We therefore use ASPCAP temperatures, available from the latest release of the APOKASC catalog (Pinsonneault et al 2014;Tayar et al 2017), to apply a zero point shift to the temperatures from SDSS and correct them for the different cluster extinctions, which were based on the KIC map (Brown et al 2011) in the work by Pinsonneault et al (2012). In this way we put the temperatures from SDSS on the same scale as ASPCAP and we adopt the typical ASPCAP total temperature uncertainty (including both systematic and random effect) of ∼69 K as a reference (see Holtzman et al, in prep.…”
Section: Effective Temperaturesmentioning
confidence: 99%